The Provision of Health Services Affects Performance of Health Personnel at Community Health Centers Hutabaginda, North Tapanuli Regency - Ismail Efendy; Endang Maryanti; Sevenris CD Butar butar (Journal of Community Health Provision, 2022)
The study aimed to investigate the impact of delivering health services on the performance of health workers at the Hutabaginda Health Centre. This study was quantitative with a cross-sectional design. The population was the Civil Servants with a minimum education of 3rd Diploma totaling 84 people. The samples taken from all population. Data analysis was performed by univariate, bivariate and multivariate analysis. The statistical test used chi-square test and logistic regression. With a p-value of 0.000<.05 for education, multiple assignments, attendance, years of service, and responsibility, it was found that education, multiple assignments, attendance, years of service, and duties influenced the performance of health professionals. Furthermore, the multiple logistic regression test reveals that education, with an odds ratio (OR) of 47,802, has a greater influence on health worker performance. It is advised that education be prioritized since it influences the performance of health professionals in delivering exceptional service that the community can be proud of (customer satisfaction), service providers, and service institutions.